Characterization of Speech and Language Phenotype in GLUT1DS - Martina Paola Zanaboni; Ludovica Pasca; Barbara Valeria Villa; Antonella Faggio; Serena Grumi; Livio Provenzi; Costanza Varesio; Valentina De Giorgis (MDPI AG, 2021)
Background: To analyze the oral motor, speech and language phenotype in a sample of pediatric patients with GLUT 1 transporter deficiency syndrome (GLUT1DS). Methods: eight Italian-speaking children with GLUT1DS (aged 4.6-15.4 years) in stable treatment with ketogenic diet from a variable time underwent a specific and standardized speech and language assessment battery. Results: All patients showed deficits with different degrees of impairment in multiple speech and language areas. In particular, orofacial praxis, parallel and total movements were the most impaired in the oromotor domain; in the speech domain patients obtained a poor performance in the diadochokinesis rate and in the repetition of words that resulted as severely deficient in seven out of eight patients; in the language domain the most affected abilities were semantic/phonological fluency and receptive grammar. Conclusions: GLUT1DS is associated to different levels of speech and language impairment, which should guide diagnostic and therapeutic intervention. Larger population data are needed to identify more precisely a speech and language profile in GLUT1DS patients.